Pseudotomentella badjelanndana, Pseudotomentella sorjusensis and Tomentella viridibasidia—three new corticioid Thelephorales species from the Scandes Mountains - Svantesson, Sten; Larsson, Karl-Henrik; Larsson, Ellen (Phytotaxa, 2021)
One Tomentella and two Pseudotomentella species are described from alpine areas of Sweden and Norway. Tomentella viridibasidia sp. nov. is genetically closely related to T. bryophila, but is morphologically most similar to T. olivascens and T. stuposa. Pseudotomentella badjelanndana sp. nov. and P. sorjusensis sp. nov. belong to the P. tristis group. At least P. sorjusensis must currently be regarded as morphologically cryptic with P. rotundispora. Basidiomata of the new species have only been encountered in the Scandes Mountains, but root-tip and soil sequences indicate that all three are geographically widespread. An updated key to the Pseutomentella tristis group is provided.